TDCS augments decision-making efficiency in an intensity dependent manner: A training study. (5th November 2022) - Ehrhardt, Shane E.; Ballard, Timothy; Wards, Yohan; Mattingley, Jason B.; Dux, Paul E.; Filmer, Hannah L.
Abstract: The application of transcranial direct current stimulation (tDCS) to the prefrontal cortex has the potential to improve performance more than cognitive training alone. Such stimulation-induced performance enhancements can generalize beyond trained tasks, leading to benefits for untrained tasks/processes. We have shown evidence that stimulation intensity has non-linear effects on augmenting cognitive training outcomes. However, it is currently unclear how stimulation intensity augments cognitive processing to impact training and transfer effects. Here, we applied decision-making modelling via the linear ballistic accumulator framework to understand what aspects of cognitive processes underlying speeded single-/dual-task decision-making performance change with tDCS intensity. One hundred and twenty-three participants were split into four groups: sham, 0.7 mA, 1.0 mA and 2.0 mA stimulation intensities. Participants completed four training sessions whilst tDCS was delivered. The 0.7 mA & 1.0 mA intensities provided the greatest benefit for performance (increased decision-making efficiency as measured by drift rates) on the trained task - more than sham or 2.0 mA stimulation. The latent decision components integrated both accuracy and reaction times to estimate performance more broadly. We see an inverted u-shaped function of stimulation intensity and cognitive performance in the trained-on task, where either no stimulation or too much stimulation is sub-optimal for performance. By contrast, 1.0 mA and 2.0 mA intensities led to increased drift rates in an untrained (transfer) single task. In sum, tDCS intensity non-linearly modulates cognitive processes related to decision-making efficiency. Highlights: Combining multitasking training with online tDCS can enhance cognitive performance. Training and stimulation benefits can generalize to an untrained multitask. Performance benefits were linked to decision efficacy (drift rates). tDCS dose showed non-linear relationship with performance enhancement. Low intensity tDCS led to the largest benefit in decision efficiency (drift rate).